Penyelesaian Sengketa Hibah Sebagai Akibat Penelantaran Pemberi Hibah (Studi Kasus Putusan PN Nomor 105/Pdt.G/2023/PN Gin) - I Kadek Cahya Mahardika; Anak Agung Istri Agung; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2025)
A grant is a gift given by a person to another person during his lifetime. Grant is an agreement where the grantor gives an object freely and cannot take it back according to his needs. grantee (subsidy recipient) On this basis the researcher wants to examine: 1) What are the general conditions of subsidies according to the Civil Code and 2) How is the settlement of subsidy disputes between grantors and grantees of land rights. This research uses normative research methods. The search results show the terms and conditions of the grant. There must be an agreement between the sponsor and the recipient regarding the grant. The donor or recipient is still alive, the spouse is prohibited from giving gifts, the adult is not a minor, the object already exists, the donor cannot promise. Collection of proceeds from movable and immovable property. The settlement of the concession dispute between the transferring party and the recipient of land rights can be carried out amicably in accordance with the decision of the Peace District Court Law Number 105/Pdt.G/2023/PN Gin.